Effectiveness of falls clinics: An evaluation of outcomes and client adherence to recommended interventions - Hill, Keith; Moore, K.; Dorevitch, M.; Day, L. (Wiley-Blackwell Publishing, Inc., 2008)
OBJECTIVES: To evaluate outcomes associated with falls clinic programs. DESIGN: Longitudinal. SETTING: Thirteen outpatient falls clinics in Victoria, Australia. PARTICIPANTS: Four hundred fifty-four people referred for clinic assessment (mean age±standard deviation 77.9±8.8; 73% female). INTERVENTION: After assessment, multifactorial interventions were organized to address identified risk factors. MEASUREMENTS: A Minimum Data Set was developed and used across all clinics to derive common data on falls, falls injuries, and secondary measures associated with falls risk, including balance, falls efficacy, gait, leg strength, function, and activity. All measures were repeated 6 months later. RESULTS: Clients had a high risk of falls, with 78% having had falls in the preceding 6 months (63% multiple fallers, 10% experiencing fractures from the falls). An average of 7.6±2.8 falls risk factors were identified per client. The clinic team organized an average of 5.7±2.3 new or additional interventions per client. Sixty-one percent of eligible clients returned for the 6-month assessment. At this time, there was more than a 50% reduction in falls, multiple falls, and fall injuries (P=.004) and small but significant improvements evident on secondary measures of balance, leg strength, gait speed, and confidence outcomes (P<.006). Average adherence to recommendations was 74.3%. Factors associated with higher adherence included being male, younger than 65, living with others, and having a caregiver (P<.05). CONCLUSION: This large multicenter study identified high falls risk of older people referred to falls clinics, the multifactorial nature of their presenting problems and provides preliminary evidence of positive outcomes after falls clinic management. © 2008, Copyright the Authors.